University-business collaboration as perceived by leading academics: comparing and contrasting the two most innovative Czech regions - Kadlec, Vojtěch; Blažek, Jiří (ERDKUNDE, 2015)
This article compares the nature of academia-business collaboration in the two most innovative Czech regions, where the respective regional decision-makers and universities’ representatives differ sharply in their approaches towards the commercialization of academic knowledge. An analysis of the nature of collaboration between life-science researchers in two leading Czech universities and private companies has been performed to identify whether targeted support provided at the regional and university levels can make a real difference and can overcome hindrances from the national level. In particular, the article investigates the motivation and approaches of leaders of life-science research teams to cooperation with private companies, the perceived barriers impeding such cooperation, including the strength of demand for innovation in both analyzed regions. The research identified significant differences in the perception of barriers between life scientists in Prague and South Moravia, vindicating the positive role of the South Moravian innovation strategy. Thus, researchers in South Moravia no longer face barriers preventing the emergence of cooperation with the business sector, and instead they are concerned about obstacles that stand in the way of its more intensive development.